DETERMINAN OPINI AUDIT ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH PROVINSI DI INDONESIA: DETERMINANTS OF AUDIT OPINION ON LOCAL GOVERMENT FINANCIAL STATEMENTS IN PROVINCES IN INDONESIA - Prahatiwi, Nur Hanny; Periansya, Periansya; Aryani, Yuli Antina (Universitas Riau, 2024)
The primary objective of this research is to examine which factors among legal compliance, internal control systems, and audit recommendation follow-ups exert the strongest impact on auditor opinions regarding Indonesian provincial governments between 2018 and 2022. The investigation relies on secondary data sources, specifically drawing from two key documents: the Semester II Audit Results Overview Report issued by BPK RI and the Compilation of Audit Recommendation Follow-up Monitoring Results spanning 2018-2022, accessed through BPK RI's media center. The research encompasses all 34 Provincial Financial Statements (LKPDs) across Indonesia as its sample population. Statistical analysis was conducted through binary logistic regression methodology, utilizing SPSS version 25 software. The findings reveal that when examined individually, neither the internal control system nor legal compliance demonstrated significant influence on audit opinions. However, the follow-up of audit recommendations, when analyzed separately, showed a meaningful impact on audit outcomes. When all three variables were considered collectively, the research discovered that internal control systems, legal compliance, and audit recommendation follow-ups jointly influenced the resulting audit opinions.